Review of sustainability in buildings. (February 2015) - Abdellatif, Mawada; Al-Shamma'a, Ahmed
Highlights: The paper takes a brief look at the concept of sustainability in existing UK building through the review of relevant literature. There are five main measures to reduce GHG emissions. The UK has already taken steps towards reducing greenhouse gas emissions from the building, but these steps have had a limited impact on actual emission level. This is due to a number of barriers. Abstract: At present, it is estimated that the building sector contributes up to 45% of annual greenhouse gas emissions primarily through the use of fossil fuels during their operational phase and consumes up to 40% of all energy in UK. Given the massive growth in new construction in economies in transition, and the inefficiencies of existing building stock, if nothing is done, greenhouse gas emissions from buildings will be more than double in the next 20 years. This is a review paper describe the extent and nature of sustainable buildings in UK, either within new or refurbishing old ones, in order to move away from traditional methods of construction and to look at multi-disciplinary and integrated approaches, as well as end-user perspectives.